Estudo das espécies da família Cichlidae na Bacia do Rio Tietê da coleção ictiológica do LISDEBE UFSCar - Wood, Karen Lima (Universidade Federal de São Carlos, 2016)
The diversity of fish species of family Cichlidae from the Tiete River basin and stored in Systematic Ichthyology Laboratory of the Department of Ecology and Evolutionary Biology at the Federal University of São Carlos (LISDEBE-UFSCar) collection was studied. They were collected by researchers from this laboratory , others researchers of the University and with the addition of coming ichthyological material from a large collection of fish made by researchers of the Energy Company of São Paulo (CESP) before the closure of the dams of the middle and lower Tiete River. The collections were made with the help of fishing nets in random locations in the main channel and in some tributaries of the river Tiete between the years 1975 and 2014, reaching a total of 795 individuals, comprising 8 genera and 9 species. Three species are recognized as exotic or invasive non-native and makes up a small portion of the collected individuals. The species of common and frequently cichlids were Cichlasoma paranaense, Autraloheros fascetus and Geopahagus brasiliensis whose sample is understand that these species are widely distributed across different environments and through different seasons. The work also presents an identification key of the nine species found in Tiete River Basin, being studied copies available for consultation at LISDEBE-UFSCar. For all species studied are provided illustrations, diagnoses, localizations and comments on morphological details. A discussion on the actual taxonomic situation and conservation of the Cichlidae ichthyofauna at river Tietê is also presented.
Keywords: Neotropical; Peixes água doce; Chave de identificação; Neotropical; Freshwater fishes; Identification key; OUTROS